Evaluación de la planta portátil potabilizadora de agua lluvia en la empresa Postobon S.A. (2018)
The evaluation of rainwater purification was carried out initially in the laboratories of Empresa Postobón S.A. determining the operating conditions of the portable plant; Initially, the characterization of the rainwater sample was carried out, to which the physical properties were determined, which are: turbidity, the solids between which are the total dissolved solids and the settleable solids and the conductivity. On the other hand, the chemical properties were also evaluated, which are: pH, hardness, alkalinity, iron and manganese content and also the free chlorine content. Then a microbiological analysis was carried out which involved the following processes: sterilization, sample collection and finally for the determination of total and fecal coliform groups, pseudomonas bacteria and mesophilic bacteria where the presence and absence method was used.